2010
DOI: 10.1177/1534735410377198
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on the Antileukemia Effects of Gypenosides In Vitro and In Vivo

Abstract: Purpose. Gypenosides (Gyp), found in Gynostemma pentaphyllum Makino, have been used as folk medicine for centuries and have exhibited diverse pharmacological effects, including antileukemia effects in vitro and in vivo. In the present study, Gyp were used to examine effects on cell viability, cell cycle, and induction of apoptosis in vitro. They were administered in the diet to mice injected with WEHI-3 cells in vivo. Experimental design. Effects of Gyp on WEHI-3 cells were determined by flow cytometric assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 28 publications
(41 reference statements)
1
24
0
Order By: Relevance
“…Gyp has been used as traditional Chinese herbal medicine for hundreds of years because of its variety of health benefits [20][22]. In the present study, Gyp induced apoptosis in human colorectal cancer SW-480 cells was investigated.…”
Section: Discussionmentioning
confidence: 94%
“…Gyp has been used as traditional Chinese herbal medicine for hundreds of years because of its variety of health benefits [20][22]. In the present study, Gyp induced apoptosis in human colorectal cancer SW-480 cells was investigated.…”
Section: Discussionmentioning
confidence: 94%
“…seeds showed anti-tumor activities under in-vivo conditions (Atashrazm et al, 2016; Liu G. et al, 2016; Zheng et al, 2016; Wang et al, 2017). One latest review updated the anti-cancerous potential of gynostemma polysaccharide in different normal and transgenic cancer mice models (Hsu et al, 2011; Lu et al, 2012; Liu et al, 2014; Tai et al, 2016). Thus, in-vivo studies using tested polysaccharide fractions at the next level would generate their comprehensive efficacy report for better prediction of their anti-cancerous potential.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review has reported the anti-cancerous mechanism of Gynostemma pentaphyllum (Thunb.) Makino (Jiaogulan) GPM polysaccharides through cell cycle arrest (modulation of several cell cycle regulatory proteins (CDK-2, CDK-4, and CDK-6) (Chen et al, 2009; Cheng et al, 2011), induction of apoptosis (regulation of anti-apoptotic proteins Bcl-2, Bcl-xl and pro-apoptotic proteins Bax, Bad, and Bak (Wang et al, 2002; Hsu et al, 2011; Lin et al, 2011; Lu et al, 2012), glycolysis inhibition and immunomodulation.…”
Section: Introductionmentioning
confidence: 99%
“…Gypenosides (Gyp), saponins extracted from G. pentaphyllum , have shown a wide range of beneficial biological activities such as cholesterol-lowering, hypoglycemic, antioxidant and immune-potentiating effects [1619]. Besides, fewer reports have described the anti-tumor activity of Gyp [2022]. However, the specific functional component of Gyp and the detailed mechanism remain unclear.…”
Section: Introductionmentioning
confidence: 99%